Pengaruh Uang Saku, Pendidikan Keuangan Keluarga dan Gaya Hidup Terhadap Pengelolaan Keuangan Pribadi Melalui Literasi Keuangan sebagai Variabel Intervening - Maria Fatima Yosefa; Christien C. Foenay; Chrispy Theresia Pratiwi Daud; Efandri Agustian (JUMANJI (JURNAL MANAJEMEN JAMBI), 2026)
Along with rapid economic development and growth accompanied by technological advances in the digital era, financial understanding is increasingly needed by both individuals and society. An understanding of financial management can serve as a foundation for managing personal finances. Based on this background, this study aims to examine and analyze the effect of allowance, family financial education, and lifestyle on personal financial management, with financial literacy as an intervening variable. This study employs a quantitative approach. The sample consists of 84 respondents who are boarding house students living in RT 17, Penfui Timur Village. The sampling technique used in this study is the Slovin formula. The data analysis technique applied is PLS-SEM (Partial Least Square–Structural Equation Modeling). Data processing was carried out using SmartPLS 4.0 software. The results of this study indicate that allowance has a positive and significant effect on the personal financial management of boarding house students, with a P-value of (0.021). Family financial education also has a positive and significant effect on personal financial management, with a P-value of (0.019). Lifestyle does not have a significant effect on personal financial management, with a P-value of (0.372). Allowance does not have a significant effect on financial literacy, with a P-value of (0.305). Family financial education does not have a significant effect on financial literacy, with a P-value of (0.069). Lifestyle does not have a significant effect on financial literacy, with a P-value of (0.069). Financial literacy has a positive and significant effect on personal financial management, with a P-value of (0.000). Allowance does not have a significant effect on personal financial management when mediated by financial literacy, with a P-value of (0.302). Family financial education does not have a significant effect on personal financial management when mediated by financial literacy, with a P-value of (0.068). Lifestyle does not have a significant effect on personal financial management when mediated by financial literacy, with a P-value of (0.437).